The safety thickness of blast furnace hearth lining and simulation analysis for different interventions. (January 2019) - Chen, J F; Chen, L Y; Li, Y
Abstract: In the late period of the blast furnace operation, the residual thickness of the hearth lining is insufficient. To avoid the burning through of hearth, intervention measures with variable operating conditions are needed. Plugging wind gap, adding Titanium ore and controlling production are frequently used at the scene of the project. A 1-D method is used to determine the safe thickness of the hearth lining. A general CFD software FLUENT is used to simulate the iron tapping of the hearth model under different interference conditions. The influence of different conditions on erosion state of the hearth is explored.